An Approach to Understanding Aggression and Human Violence - Yañez Canal, Humberto (Pensando Psicología, 2015)
Purpose: To reflect on certain possible confusions that arise in the social and communicative practice of professionals in the field of education and social treatment when dealing with school violence. A review of the matter showed that some of the basic confusions seem to arise around the use of the concepts of aggression and violence, which some authors treat as though they were synonyms, ignoring efforts by the social sciences to understand and explain them. The purpose of this text is to deal with this confusion and present options for understanding the implications of these two terms. Topic: Dealing with school violence has been on the agenda over the past two years. Repeatedly, extreme cases are published asking experts to provide explanations and solutions, although it seems that violent practices persist and efforts have been insufficient. Development: Confusions in the definitions that appear in dictionaries are examined, etymological significances are addressed and the use and meaning of aggression and violence from the perspective of sociology, politics and psychology are reviewed. Conclusions: A review of the two concepts is proposed in which their differences are established, but which is based on the same phenomenon expressed in gradual intensities and frequencies. The text also seeks to recognize that all movements in limited spaces are susceptible to being perceived as aggressive by whoever is subjected to that force.